2018
DOI: 10.3389/fendo.2018.00255
|View full text |Cite
|
Sign up to set email alerts
|

ZNF423: A New Player in Estrogen Receptor-Positive Breast Cancer

Abstract: Preventive therapy can target hormone-responsive breast cancer (BC) by treatment with selective estrogen receptor modulators (SERMs) and reduce the incidence of BC. Genome-wide association studies have identified single nucleotide polymorphisms (SNPs) with relevant predictive values, SNPs in the ZNF423 gene were associated with decreased risk of BC during SERM therapy, and SNPs in the Cathepsin O gene with an increased risk. ZNF423, which was not previously associated with BC is a multifunctional transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…The first fifteen genes that were significantly hypomethylated on different sites across the genome in cancer tissues in comparison to control healthy tissues, named ATXN1 , PPP2R2C , CCR6 , RAB37 , DUSP27 , ZNF521 , SLC6A17 , SPIN1 , CXCR1 , SPTBN1 , NBAS , NRG3 , COL5A1 , CDX1 , and BATF3 are mostly involved in transcriptional and immune regulation. Among this group of genes, aberrantly methylated in other human cancers were CCR6 in oral cancer [ 38 ] and chronic lymphocytic leukemia [ 39 ], RAB37 in lung cancer [ 40 ], ZNF521 in breast cancer [ 41 ], and CDX1 in gastric cancer [ 42 ], esophageal SCC [ 43 ], and in colon cancer [ 44 ]. The genes involved in the immune regulation could belong to the tumor-infiltrating immune cells or tumor-infiltrating lymphocytes, which are often associated with better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The first fifteen genes that were significantly hypomethylated on different sites across the genome in cancer tissues in comparison to control healthy tissues, named ATXN1 , PPP2R2C , CCR6 , RAB37 , DUSP27 , ZNF521 , SLC6A17 , SPIN1 , CXCR1 , SPTBN1 , NBAS , NRG3 , COL5A1 , CDX1 , and BATF3 are mostly involved in transcriptional and immune regulation. Among this group of genes, aberrantly methylated in other human cancers were CCR6 in oral cancer [ 38 ] and chronic lymphocytic leukemia [ 39 ], RAB37 in lung cancer [ 40 ], ZNF521 in breast cancer [ 41 ], and CDX1 in gastric cancer [ 42 ], esophageal SCC [ 43 ], and in colon cancer [ 44 ]. The genes involved in the immune regulation could belong to the tumor-infiltrating immune cells or tumor-infiltrating lymphocytes, which are often associated with better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZNF423 could promote adipogenesis via the peroxisome proliferator-activated receptor γ (PPARγ) pathway [6,7]. Besides, this protein has been identified as an important transcriptional modulator in several types of cancer, such as acute lymphoblastic leukemia (ALL) [8], chronic myelogenous leukemia (CML) [9], nasopharyngeal carcinoma (NPC) [10], neuroblastoma (NB) [11], and breast cancer (BC) [12,13]. In ALL, ZNF423 inhibits transcriptional factor of B-cell differentiation (EBF1) leading to B-cell maturation arrest [8].…”
Section: Introductionmentioning
confidence: 99%
“…ZNF423 is likely involved with centrosomes and DNA damage repair [26]. It is downregulated in human neuroblastoma and glioma [52] [53] and also has a role in breast cancer [54]. Previously, it also has been shown that missense and LoF variants are likely to be pathogenic for abnormality of brain morphology, Joubert syndrome and Nephronophthisis with autosomal dominant or autosomal recessive inheritance (www.omim.org, https://www.ncbi.nlm.nih.gov/clinvar/).…”
Section: Discussionmentioning
confidence: 99%